Importance of post-translational modifications on the function of key haemostatic proteins. Issue 1 (January 2016) - Karlaftis, Vasiliki; Perera, Sachin; Monagle, Paul; Ignjatovic, Vera
Abstract : Post-translational modifications (PTMs) such as glycosylation and phosphorylation play an important role on the function of haemostatic proteins and are critical in the setting of disease. Such secondary level changes to haemostatic proteins have wide ranging effects on their ability to interact with other proteins. This review aimed to summarize the knowledge of the common PTMs associated with haemostatic proteins and the implications of such modifications on protein function. Haemostatic proteins that represent the main focus for studies specific to PTMs are von Willebrand factor, tissue factor, factor VIII, antithrombin and fibrinogen. These proteins are susceptible to PTMs by glycosylation, phosphorylation, sulphation, citrullination and nitration, respectively, with a significant impact on their function. During synthesis, vWF must undergo extensive PTMs, with N-linked glycosylation being the most common. Increased phosphorylation of tissue factor results in increased affinity for platelets to the vessel endothelium. Citrullination of antithrombin leads to an increased anticoagulant function of this protein and therefore an anticoagulant state that inhibits clot formation. On the contrary, nitration of fibrinogen has been shown to result in a prothrombotic state, whilst sulphation is required for the normal function of Factor VIII. From this review, it is evident that PTMs of haemostatic proteins as a change in protein structure at a secondary level greatly influences the behaviour of the protein at a tertiary level.